Identity Politics and Political Parties in India - Pinatih, IGAAG Dewi Sucitawathi (Nation State: Journal of International Studies, 2024)
India is the country with the largest Hindu majority in the world. Since the Bharatiya Janata Party (BJP) came to power, the leadership model in India has been directed at implementing the teachings of Hindu nationalism, which considers it essential to protect Indian Hindu culture from the attacks of Western liberal ideology. This research aims to provide an overview of how Hindu identity politics is implemented in India under the rule of the BJP and what kind of political strategies and policies have been created by the Indian government, influenced by the ideology of Hindu hypernationalism. This qualitative research uses literature review data analysis techniques. The data sources used are secondary data from journals, books, and websites related to the research theme. Source triangulation is used for data validity, namely by verifying different data sources to obtain valid results. This research found that the identity politics implemented by the BJP utilizes the belief system/ideology of Indian Hindus through Hindutva teachings. The political strategy is carried out by embracing as many radical Hindu groups as possible and creating various policies that discredit minority groups in India. Additionally, during campaigns, the BJP often uses Hindu symbols to gain political support.